2013
DOI: 10.1111/jog.12147
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial comparing efficacy between a vaginal misoprostol loading and non‐loading dose regimen for second‐trimester pregnancy termination

Abstract: Vaginal misoprostol in the loading dose regimen had a similar efficacy to the non-loading dose regimen but was associated with more adverse maternal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…In second-trimester procedures, repeat doses of misoprostol are typically administered without mifepristone until expulsion occurs, leading to successful completion in 26%-96% of women, depending on the dose, dosing interval, route, and allowed time to completion (many only document completion up to 15 hours after initiation of misoprostol) [9][10][11][12][13][14][15]. Regimens that include mifepristone before misoprostol have demonstrated completion rates of 63%-100% and typically result in shorter times to expulsion [6,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…In second-trimester procedures, repeat doses of misoprostol are typically administered without mifepristone until expulsion occurs, leading to successful completion in 26%-96% of women, depending on the dose, dosing interval, route, and allowed time to completion (many only document completion up to 15 hours after initiation of misoprostol) [9][10][11][12][13][14][15]. Regimens that include mifepristone before misoprostol have demonstrated completion rates of 63%-100% and typically result in shorter times to expulsion [6,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…We did not find any study comparing different doses of vaginal misoprostol regimens in the first trimester of pregnancy, however, a randomized controlled trial by Pongsatha et al 25 compared the vaginal misoprostol loading and non-loading dose regimens and revealed that a loading dose of misoprostol was significantly related to higher rates of adverse effects and comparable success rate, they concluded that loading dose of misoprostol is not more effective than non-loading dose to induce abortion in second trimester, 25 that was in contrast to all studies ,evaluating the misoprostol effect, on the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 83%
“…Pongsatha 7 et al compared a vaginal misoprostol LD regimen (600 mcg, then 400 mcg 6 hourly) with a nonloading dose regimen (400 mcg 6 hourly) in 157 women and found both equally effective with adverse drug effects associated more with loading dose regimens.…”
Section: Discussionmentioning
confidence: 99%